The radical enlightenment in Germany : a cultural perspective - Niekerk, Carl (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, 2018)
This volume investigates the impact of the Radical Enlightenment on German culture during the eighteenth century, taking recent work by Jonathan Israel as its point of departure. The collection documents the cultural dimension of the debate on the Radical Enlightenment. In a series of readings of known and lesser-known fictional and essayistic texts, individual contributors show that these can be read not only as articulating a conflict between Enlightenment and Counter-Enlightenment, but also as documents of a debate about the precise nature of Enlightenment. At stake is the question whether the Enlightenment should aim to be an atheist, materialist, and political movement that wants to change society, or, in spite of its belief in rationality, should respect monarchy, aristocracy, and established religion. Contributors are: Mary Helen Dupree, Sean Franzel, Peter Höyng, John A. McCarthy, Monika Nenon, Carl Niekerk, Daniel Purdy, William Rasch, Ann Schmiesing, Paul S. Spalding, Gabriela Stoicea, Birgit Tautz, Andrew Weeks, Chunjie Zhang.